Microbial regulation of nutrient cycling potential and soil amelioration after Morchella cultivation in saline-alkali soils of Ningxia - Yifan Wu; Xiaoli Yang; Yaya Zhang; Chunyan Xu (Applied Soil Ecology, 2026)

Asparagus Polysaccharide Ameliorates TNF-α-Mediated MH7A Cell Dysfunction and Collagen-Induced Arthritis in Mice - Mingfeng Yang; Fangyan Xu; Bin Zhang; Lijun Xu (Cell Biochemistry and Biophysics, 2026)

miR-4632-5p Alleviates Lumbar Disc Degeneration by Targeting MAP3K11: A Novel Role in Mitigating Nucleus Pulposus Cell Degeneration - Xinfei Lan; Haiyan Xue; Mianlong Lin; Jinxiang Zhang; Qingfeng Zhang; Canhua Xu (Biochemical Genetics, 2026)

Varietal traits of Lycium barbarum cultivars structure rhizosphere microbial communities and influence root rot susceptibility - Chenbo Jia; Shuxuan Liu; Jianyu Su; Chunyan Xu (Applied Soil Ecology, 2026)

Earthworm stress adaptation: The pivotal role of viruses in microplastic‑cadmium co-exposure - Yucui Ning; Yuze Li; Houyu Guo; Jingyang Sun; Jiaqi Xue; Yan Xu; Zhuyun Li; Detang Zou; Dongxing Zhou (Applied Soil Ecology, 2026)

Effects of nitrogen fertilizer replacement with different sourced-black soldier fly frass on rice growth, physiological characteristics and soil properties - Yajing Cao; Nan Wu; Lijun Shi; Xiaoyan Xu; Xiaobo Wang (Applied Soil Ecology, 2025)

The feeding ecology of grass carp: A review - Lisen Li; George Balto; Xiaoyan Xu; Yubang Shen; Jiale Li (Reviews in Aquaculture, 2023)
As an economically important herbivorous fish, the range of grass carp ( Ctenopharyngodon idella ) has expanded in the world and its ecological influences have become more evident. Currently, we have embarked on assessing the effect of grass carp on aquatic organisms and water quality by integrating the outcomes from previous ecological studies. Bibliographical data integration shows that aquatic plant preference is likely to be related to the cellulose proportion, calcium, sucrose and citric acid of the aquatic plant. Moreover, pharyngeal teeth and multiple gene copies of taste receptors could help reveal the feeding mechanism of grass carp. The expansion of the number of sweet‐detecting T1R2 genes, and the functional potential of Umami taste receptor T1R3 by calcium‐regulation was speculated on the basis of previous experimental observations of grass carp, suggesting that aquatic plant consumption by this species is tightly associated with the taste receptors. Apart from the competition in living space between grass carp and other fish, the effects of consuming zooplankton and zoobenthos were summarized to reveal general passive feeding of grass carp, as well as the feeding choice in the absence of aquatic plants. Water quality data were gleaned to make comparative analyses between groups stocking with and without grass carp to uncover changes in water physicochemical parameters in short‐ (